Cytotoxicity of selected organotin (IV) compounds on vero and caov-3 cell lines - Siti Farizah, Wagimen (Universiti Malaysia Sarawak, UNIMAS, 2010)
Organotin(IV) compounds have been known to possess biological activities including antimicrobial, antiviral and anticancer. These compounds were previously been synthesized by chemistry department of FRST, UNIMAS. The objective of this study was to screen selected organotin(IV) compounds for cytotoxicity effect on Vero cells and Caov-3 cells. These compounds showed high cytotoxicity effect on Vero cells when incubated for 72 hours compare to 48 hours incubation time. Most of the compounds were found to inhibit the growth of Caov-3 cell lines by 50% through cytotoxicity test using MTT assay. The value was detected through 48 hours incubation and 72 hours incubation in which 72 hours incubation showed the lowest value that is in range 5 ug/mL to 14 ug/mL. The pyruvic acid showed the lowest percentage of cell viability that is 33.1% for 48 hours incubation at concentration 100 μg/mL The pyruvic acid also showed the lowest value among the compounds that is 32 μg/mL while diphenyltin(IV) monochloride showed the highest value (64 μg/mL) compare to others. Monomethyltin(IV) dichloride and monophenyltin(IV) dichloride have been found to have potential as anticancer drug.